If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 23 = 32 Reorder the terms: 23 + -5x = 32 Solving 23 + -5x = 32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + -5x = 32 + -23 Combine like terms: 23 + -23 = 0 0 + -5x = 32 + -23 -5x = 32 + -23 Combine like terms: 32 + -23 = 9 -5x = 9 Divide each side by '-5'. x = -1.8 Simplifying x = -1.8
| 7(x-1)=5(x-15) | | ln(8x-7)=2 | | 8x+44=100 | | 10x+(16y+6)=180 | | 2z+3z= | | -5(x+4)+6=-3(2x+2)+x | | 4x^2+256=y | | 2(3x-51)-x=10-3x | | 22=-14+2x | | -7h-5=-4-4h | | 4z+9z-2z=10 | | 7(x-2)=(x+3) | | 4x+8=20-7x | | 2y+15=3y-1 | | -90=6(7n-1) | | 23X-2=16X+51 | | 1x(3x-10)=90 | | y=0.5x+6.18 | | 5(x-11-7)=16 | | 5x+2+7x=180 | | 5+18=35 | | x=38+x | | 4p-13p+1p=-150 | | 60=3*2y+3*4 | | 2(x-5)-6x=-22 | | X+7=x+(-2) | | -59+x= | | 3z+5=3z+5 | | 9(x+5)=3(x-3)+6x | | 3z+5+6z+4=9z+9 | | x-59= | | 8r+3s=66 |